Design structure matrix methods and applications - Eppinger, Steven D. (MIT Press, 2012)
An introduction to a powerful and flexible network modeling tool for developing and understanding complex systems, with many examples from a range of industries.
Keywords: Product design.; Systems engineering.; Flexible manufacturing systems.; elektronické knihy; electronic books